Playwork practice as action research. (1st June 2018) - Newstead, Shelly; Worch, Rick; Brahier, Daniel
Abstract : The playwork profession is currently suffering from an international identity crisis as a result of being unable to justify its own existence for the last 70 years. While playwork authors have often blamed playwork's lack of status and recognition on external factors, such as lack of public understanding and government support, this article argues that playwork's perennial problem lies in the profession's inability to define and secure its own professional knowledge base. An innovative solution to playwork's prolonged identity crisis is proposed, by conceptualising playwork practice as a form of action research. The steps of a playwork-appropriate action research approach are outlined and aligned to hands-on playwork practice to illustrate how the practice of playwork creates and develops a body of knowledge that is unique to the playwork profession. The authors conclude that a more rigorous approach to describing playwork as both practice and research would enable playwork practitioners to develop a common approach to their work and a professional language with which to describe playwork in its own terms, thereby establishing a unique identity for playwork within the wider international children's workforce.